Effect of additive type D and F on concrete strength capacity by using aggregate type, size, and content: Lumajang sand – Bangkalan gravel - Pertiwi, D; Soebagio, Soebagio; Rudianto, E (Institut Teknologi Sepuluh Nopember, 2018)
Bangkalan district has the potential unallocated aggregate to be applicated as a concrete mixture in the form of fine aggregates (sand) and coarse aggregates (gravel). In fact, Bangkalan aggregate implies excellent structure, so this material is rarely used as a mixture of concrete because with its fine structure the quality of the concrete produced will be less good. To maximize the use of aggregates from Bangkalan, a concrete mixture design analysis is conducted. The study is based on a test of the physical properties which are classified into five variations. Variation one implies a combination of 5/10 and 10/20 use of gravel and sand from Bangkalan when modification two only change the subject of Bangkalan sand to Lumajang sand with the same proportion. Variation three is treated a combination two with a given 0.3% of additive type D. The variation is increased to be added more additive in variation four with 0.6 % type F. As a final variation, with the same proportion of Lumajang sand and Bangkalan gravel of 5/10 and 10/20 combined with 0.3% additive type D and 0.6% additive type F. The capacity is compared based on physical properties and compression test. As a result, the best proposed design is variation three with a compression test over standard design with 29.44 MPa.